2016
DOI: 10.1118/1.4939261
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of photon beam dosimetry for a linear accelerator

Abstract: This novel analytical model with minimum measurement requirements was proved to accurately calculate PDDs, profiles, and S(cp) for different field sizes, depths, and energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In our previous work, we demonstrated that the penumbra region (P) can be characterized with a modified sigmoid function,Pfalse(rfalse)=italicβ1italicβ21+erα1italicα2where r is the radial distance from the CAX; α and β are field size‐, energy‐ and depth‐dependent parameters. The physical meaning of the parameters and the method to segment the profiles can be found in our previous paper . We have demonstrated that this function can successfully parameterize the penumbra region of beam profiles with field sizes ranging from 2 × 2 to 40 × 40 cm .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work, we demonstrated that the penumbra region (P) can be characterized with a modified sigmoid function,Pfalse(rfalse)=italicβ1italicβ21+erα1italicα2where r is the radial distance from the CAX; α and β are field size‐, energy‐ and depth‐dependent parameters. The physical meaning of the parameters and the method to segment the profiles can be found in our previous paper . We have demonstrated that this function can successfully parameterize the penumbra region of beam profiles with field sizes ranging from 2 × 2 to 40 × 40 cm .…”
Section: Methodsmentioning
confidence: 99%
“…The physical meaning of the parameters and the method to segment the profiles can be found in our previous paper . We have demonstrated that this function can successfully parameterize the penumbra region of beam profiles with field sizes ranging from 2 × 2 to 40 × 40 cm . Figure (a) shows the penumbra region to be fitted with Eq.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, interpolation and correlation can be used to incorporate data published by other sources into the model, thereby reducing the number of measurements that needs to be collected on site. LeBron et al [9] echo this assertion by advocating the portability of data sets and the ease of evaluating the characteristics of different materials. For instance, Du Plessis et al [7] present a detailed analysis of linear attenuation measurements in several materials with different atomic numbers.…”
Section: Introductionmentioning
confidence: 90%